Analisis Faktor yang Membentuk Kepatuhan Wajib Pajak Kendaraan Bermotor pada Kantor Bersama Samsat Praya - Sabirin Alam (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Tax compliance is a condition where taxpayers fulfill all tax obligations and exercise their tax rights. This research aims to identify the main factors that shape taxpayer compliance in the office of the joint Samsat Praya. This study uses primary data with data collection techniques carried out by distributing questionnaires to taxpayer respondents. The number of samples used was 150 respondents. The research method used is factor analysis using the Principal Component Analysis (PCA) approach. The results showed that the 19 variables analyzed produced five main factors that we're able to explain 61.712% of the factors causing motor vehicle taxpayer compliance in the office of the joint Samsat Praya. Of the 5 main factors formed, there are two internal factors and three external factors that affect the compliance of motor vehicle taxpayers in the office of the joint Samsat Praya. Internal factors that are formed are Knowledge and Understanding of Taxes and Awareness of Taxpayers with external factors which include Quality and Service, Compliance, and Warnings and Sanctions.